Influence of transformational leadership on affective commitment and job performance: mediation by engagement and trust - Lamin Saidyjeng; Riani Rachmawati (Universitas Nusa Cendana, 2026)
This study examines the effects of transformational leadership on affective organizational commitment and job performance, while investigating the parallel mediating roles of employee engagement and trust in leadership among academic and administrative staff at the University of The Gambia. Using survey data from 201 respondents and Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis, the findings reveal that transformational leadership positively and significantly influences employee engagement, trust in leadership, and affective organizational commitment. However, no direct effect on job performance was observed. The results further demonstrate that employee engagement and trust in leadership significantly mediate the relationship between transformational leadership and job performance, while partially mediating the relationship with affective organizational commitment. These findings suggest that transformational leaders enhance employee outcomes indirectly by cultivating trust and fostering engagement. This study contributes empirical evidence from a West African higher education context, offering practical implications for university administrators seeking to strengthen staff retention and institutional effectiveness through leadership development initiatives. Keywords: Transformational Leadership; Employee Engagement; University of The Gambia; Affective Organizational Commitment